Memaknai Negara, Agama, dan Ideologi Politik dalam Kajian Fiqih Kontemporer - Yudi Surono, Lc., MHI; Anita, M.Ag; Dr. Diana, M.Pd.I (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2024)
This article discusses the meaning of the relationship between state, religion and political ideology in contemporary jurisprudence studies. By paying attention to evolving socio-political dynamics, this article explores the role and interaction of these three entities in the context of modern Muslim society. This research uses a qualitative approach with a library research method. The research design used is descriptive-analytical. The data sources in this research consist of two types, namely 1) Primary Data: Even though this research is library research, the primary data is in the form of writings. from contemporary fiqh scholars, relevant official state documents, and fatwas related to the research theme will be used. 2) Secondary Data: Secondary data includes books, journal articles, research reports, and other academic sources that have discussed related topics. Using a fiqh approach, this article analyzes how fiqh concepts influence views on the role of the state, the role of religion in politics, and the implementation of political ideology in government. Through a critical review of contemporary literature and discourse, this article aims to provide in-depth insight into how understanding of this relationship is developing in the context of changing times